Inflammatory bowel disease-specific health-related quality of life instruments: a systematic review of measurement properties - Chen, Xin-Lin; Zhong, Liang-huan; Wen, Yi; Liu, Tian-Wen; Li, Xiao-Ying; Hou, Zheng-Kun; Hu, Yue; Mo, Chuan-wei; Liu, Feng-Bin (Health and quality of life outcomes, 2017)
This review aims to critically appraise and compare the measurement properties of inflammatory bowel disease (IBD)-specific health-related quality of life instruments. Medline, EMBASE and ISI Web of Knowledge were searched from their inception to May 2016. IBD-specific instruments for patients with Crohn's disease, ulcerative colitis or IBD were enrolled. The basic characteristics and domains of the instruments were collected. The methodological quality of measurement properties and measurement properties of the instruments were assessed. Fifteen IBD-specific instruments were included, which included twelve instruments for adult IBD patients and three for paediatric IBD patients. All of the instruments were developed in North American and European countries. The following common domains were identified: IBD-related symptoms, physical, emotional and social domain. The methodological quality was satisfactory for content validity; fair in internal consistency, reliability, structural validity, hypotheses testing and criterion validity; and poor in measurement error, cross-cultural validity and responsiveness. For adult IBD patients, the IBDQ-32 and its short version (SIBDQ) had good measurement properties and were the most widely used worldwide. For paediatric IBD patients, the IMPACT-III had good measurement properties and had more translated versions. Most methodological quality should be promoted, especially measurement error, cross-cultural validity and responsiveness. The IBDQ-32 was the most widely used instrument with good reliability and validity, followed by the SIBDQ and IMPACT-III. Further validation studies are necessary to support the use of other instruments.